Biotransformation in Double-Phase Systems: Physiological Responses of Pseudomonas putida DOT-T1E to a Double Phase Made of Aliphatic Alcohols and Biosynthesis of Substituted Catechols - Rojas, Antonia (American Society for Microbiology, 2004)
Pseudomonas putida strain DOT-T1E is highly tolerant to organic solvents, with a logP(ow) (the logarithm of the partition coefficient of a solvent in a two-phase water-octanol system of ≥2.5. Solvent tolerant microorganisms can be exploited to develop double-phase (organic solvent and water) biotransformation systems in which toxic substrates or products are kept in the organic phase. We tested P. putida DOT-T1E tolerance to different aliphatic alcohols with a logP(ow) value between 2 and 4, such as decanol, nonanol, and octanol, which are potentially useful in biotransformations in double-phase systems in which compounds with a logP(ow) around 1.5 are produced. P. putida DOT-T1E responds to aliphatic alcohols as the second phase through cis-to-trans isomerization of unsaturated cis fatty acids and through efflux of these aliphatic alcohols via a series of pumps that also extrude aromatic hydrocarbons. These defense mechanisms allow P. putida DOT-T1E to survive well in the presence of high concentrations of the aliphatic alcohols, and growth with nonanol or decanol occurred at a high rate, whereas in the presence of an octanol double-phase growth was compromised. Our results support that the logP(ow) of aliphatic alcohols correlates with their toxic effects, as octanol (logP(ow) = 2.9) has more negative effects in P. putida cells than 1-nonanol (logP(ow) = 3.4) or 1-decanol (logP(ow) = 4). A P. putida DOT-T1E derivative bearing plasmid pWW0-xylE::Km transforms m-xylene (logP(ow) = 3.2) into 3-methylcatechol (logP(ow) = 1.8). The amount of 3-methylcatechol produced in an aliphatic alcohol/water bioreactor was 10- to 20-fold higher than in an aqueous medium, demonstrating the usefulness of double-phase systems for this particular biotransformation.